Humanae Vitae: Fifty Years Later - Curran, Charles E. (Theological studies, 2018)
This article considers what has transpired in the Catholic Church on the issue of contraception in the fifty years since the encyclical Humanae Vitae in 1968. The author argues that today there are sufficient reasons to support a consideration of change in the teaching. Without such a consideration that works toward development or change in this teaching, the church risks continuing loss of credibility and will not be able to address honestly other important contemporary issues.